The problem is to find the number of rotations around the origin for the function

$$f(z)=z^{2013}+2z+1 $$ when $z$ moves through $\left\{|z|=1\right\}$.

I tried to solve it with the help of argument principle.

$${{N}_{r}}\left( {{z}^{2013}}+2z+1 \right)={{N}_{\left| z \right|<1}}\left( {{z}^{2013}}+2z+1 \right),$$ where ${{N}_{r}}$ - number of rotations around origin, ${{N}_{\left| z \right|<1}}$- number of zeros of ${{z}^{2013}}+2z+1$ in $\left\{ z:\left| z \right|<1 \right\}$. As ${{z}^{2013}}+2z+1$ is continuous function and ${{z}^{2013}}+2z+1$has no roots on $\left\{ \left| z \right|=1 \right\}$, we can use the theorem of Rouché: if we take $r=0.999999$ then $$|z^{2013}+1|<r^{2013}+1<2r=|2z| ,$$ so, there is only 1 root in $\left\{ z:\left| z \right|<0.999999 \right\}$. But if we take $r=1.001$ and use this theorem again, $$|2z|<2r<||r|^{2013}-|1||\le|z^{2013}+1|,$$ so, in $\left\{|z|<1.001\right\}$ there are 2013 roots. But how many roots are there in $\left\{1<|z|<1.001\right\}$ and $\left\{0.999999<|z|<1\right\}$ -- is unknown. Anything usefull will be appreciated.


We note that $z=-1$ isn't a zero of $z^{2013}+2z+1$, therefore it doesn't vanish in some $D_{2\varepsilon}(-1)$. Consider the path $\gamma$ which tours the unit circle, except staying at distance $\varepsilon$ from $-1$. Along that curve, $|z^{2013}|\leq 1<|2z+1|$, hence $z^{2013}+2z+1$ has the same number of zeroes inside $\gamma$ (and therefore inside $S^1$) as $2z+1$, namely $1$.

  • $\begingroup$ Great! It's that one step with which I could not come up. $\endgroup$ – cool Aug 6 '13 at 13:29
  • $\begingroup$ I should have specified, you have to bypass $-1$ inside the unit disc, for the inequalities to hold. $\endgroup$ – Jonathan Y. Aug 6 '13 at 14:45
  • $\begingroup$ It was obvious. $\endgroup$ – cool Aug 6 '13 at 15:50
  • $\begingroup$ Yes, yes, but I think someone asked about it in a comment that's no longer there. $\endgroup$ – Jonathan Y. Aug 6 '13 at 15:53

If you don't only look at the statement of Rouché's theorem, but also at the proof, you will notice that the condition $\lvert f(z) - g(z)\rvert < \lvert g(z)\rvert$ on $\partial V$ is only used to guarantee that

$$g(z) + \lambda \bigl(f(z) - g(z)\bigr) = (1-\lambda)g(z) + \lambda f(z)$$

has no zeros on $\partial V$ for $0 \leqslant \lambda \leqslant 1$. That weaker condition is all that is needed to have the conclusion of the theorem.

Here, with $f(z) = z^{2013} + 2z + 1$ and $g(z) = 2z+1$, we have $\lvert f(z) - g(z) \rvert = \lvert z\rvert^{2013} = 1 \leqslant \lvert g(z)\rvert$ on $C = \{\lvert z\rvert = 1\}$, and equality holds only at $z = -1$, where we have $f(-1) = -2$ and $g(-1) = -1$, so $(1-\lambda)g(z) + \lambda f(z)$ has no zeros on $C$, and the conclusion of the theorem holds.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.